Use of Realia Media to Improve Children's Mathematics Learning Outcomes in Paud Permata Iman - 1585, Listiani (Journal of Childhood Education, Development and Parenting, 2023)
This research was conducted on Permata Iman PAUD children whose background was the low learning outcomes of children in mathematics.The purpose of this study was to improve children's mathematics learning outcomes with the help of realia media in the form of coloredpaper. This research was conducted using action research methods with 2 cycles. In cycle I, an average value of 66.20 was obtained.In cycle 1, only 13 people reached the KKM out of a total of 24 children. In the second cycle, an average value of 79.62 was obtained andall children achieved KKM scores and some even exceeded it. From these results it can be concluded that the use of realia media can improvethe mathematics learning outcomes of Permata Iman PAUD children. This can also be proven by showing the percentage of children's learningcompleteness results in cycle I of 54.16%, then increasing in cycle II to 100%.